Listening and spoken language outcomes after 5 years of cochlear implant use for children born preterm and at term. (22nd September 2021) - Robertson, Jennifer; Simoes‐Franklin, Cristina; Ferguson, Olivia; Hussey, Antonia; Costello, Patsy; Walshe, Peter; Glynn, Fergal; Viani, Laura; Gill, Irwin
Abstract : Aim: To compare listening and spoken language outcomes after cochlear implantation for children born preterm and at term, and to examine patterns associated with additional disabilities or gestational age. Method: Children were included if they underwent cochlear implantation in 2013 or 2014 and had complete 5‐year follow‐up data available. An analysis of assessment data recorded annually was conducted, including outcomes as measured by the Category of Auditory Performance (CAP), the Speech Intelligibility Rating, Second Edition (SIR 2) scale, and the British Picture Vocabulary Scales, Third Edition (BPVS‐3). Analyses were conducted to measure the impact of preterm birth and of additional causes of disability on these outcomes. Results: Eighty‐two children (39 males, 43 females; median corrected age at first cochlear implantation 28.5mo [interquartile range 16.3–48.5]) were included in the study. Children who underwent cochlear implantation experienced significant improvements as measured by the CAP, SIR 2, and BPVS‐3. Comparable improvements were seen in the groups born at term and preterm. Children with additional disabilities experienced significant improvement in all measures but performed less well than children without additional disabilities. Interpretation: Infants born preterm benefit from cochlear implantation to a degree comparable to their peers born at term. Additional disabilities may limit improvements in speech intelligibility, listening performance, and receptive vocabulary. Children with additional disabilities, nonetheless, derived significant benefit from cochlear implantation; additional benefits of cochlear implantation for this subgroup may go unmeasured by the outcome tools used in this study. Abstract : This original article is commented by Kral on page 408 of this issue.